Binasal Visual Field Defects Due to Sickle Cell Maculopathy. Issue 1 (March 2022) - Kwok, Jason M.; Jeeva-Patel, Trishal; Margolin, Edward A.
Abstract : Abstract: A 26-year-old African American man with sickle cell disease noticed blurry vision in both eyes after a recent complicated hospital admission for sickle cell crisis. Anterior and posterior segment examination of each eye was normal, but visual field testing revealed binasal scotomas. Optical coherence tomography of the macula demonstrated severe thinning of the temporal inner retina, suggesting previous bilateral occlusions of terminal retinal arterioles involving the temporal macula, an uncommon complication of sickle cell disease. This case is a reminder that retinal pathology should always be considered as a potential cause of unexplained visual field defects and highlights the role of macular OCT in evaluation of these patients.